Bridging the financial literacy gap: designing an educational unit on personal finance - Kessler, Sabrina. author; Luchs-Nunez, Jenny, advisor; Stekelberg, James, committee member (Colorado State University. Libraries, 2026)
Financial literacy is a critical skill that influences individuals’ ability to make informed financial decisions and maintain long-term economic stability. This paper examines the importance of financial literacy, the consequences of low financial knowledge, and the effectiveness of school-based financial education programs. Drawing on existing research in personal finance and education, including studies on financial behavior, credit outcomes, and financial capabilities, this paper highlights how financial education improves both financial knowledge and real-world financial behaviors, like saving, borrowing, and credit management. Evidence suggests that structured financial education at the high school level can lead to measurable improvements in credit outcomes and long-term financial health. This paper explores effective instructional methods for teaching personal finance. Research indicates that experiential learning, real-world application, and student focused instruction are essential for developing both financial competence and confidence in applying financial concepts. Strategies such as simulations, collaborative activities, and applied financial tasks help students develop practical skills and confidence in decision-making. The paper presents a comprehensive semester long high school financial literacy unit aligned with the Colorado Academic Standards. The unit emphasizes progressive skill development, multiple forms of assessment, including a summative project that requires students to apply financial concepts in a realistic scenario. This paper argues that integrating structured, applied financial literacy education into high school curriculum is an effective approach to preparing students for real-world financial responsibilities and promoting long-term financial capability.
Keywords: personal finance; accounting; finance; education unit